ATM traffic management in an LMDS wireless access network. - Kuri, J. (IEEE Communications magazine)
We investigate the capacity of LMDS to support ATM services in the local loop. In particular, we evaluate the performance of a MAC protocol for this system when transporting voice and IP traffic using the VBR and GFR service categories of ATM, respectively. Our results show that the MAC protocol is well suited for voice traffic but in general lacks efficient bandwidth management mechanisms to support the more dynamic bandwidth requirements of IP traffic